Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Solve for [tex]\( x \)[/tex]:

[tex]\[
\sqrt{6x + 46} - 18 = -16
\][/tex]

[tex]\( x = \)[/tex] [tex]\(\square\)[/tex]


Sagot :

To solve the equation [tex]\(\sqrt{6x + 46} - 18 = -16\)[/tex] for [tex]\(x\)[/tex], follow these steps:

1. Isolate the square root term:
[tex]\[ \sqrt{6x + 46} - 18 = -16 \][/tex]
Add 18 to both sides of the equation:
[tex]\[ \sqrt{6x + 46} = -16 + 18 \][/tex]
Simplify the right side:
[tex]\[ \sqrt{6x + 46} = 2 \][/tex]

2. Eliminate the square root by squaring both sides:
[tex]\[ (\sqrt{6x + 46})^2 = 2^2 \][/tex]
This simplifies to:
[tex]\[ 6x + 46 = 4 \][/tex]

3. Solve for [tex]\( x \)[/tex]:
Subtract 46 from both sides:
[tex]\[ 6x = 4 - 46 \][/tex]
Simplify the right side:
[tex]\[ 6x = -42 \][/tex]
Divide both sides by 6:
[tex]\[ x = \frac{-42}{6} \][/tex]
Simplify the fraction:
[tex]\[ x = -7 \][/tex]

Therefore, the solution to the equation is:

[tex]\[ \boxed{-7} \][/tex]